2015
DOI: 10.1016/j.ajme.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological assessment ofBurkholderia cepaciacomplex (Bcc) isolates in Alexandria Main University Hospital

Abstract: Nosocomial spread of B. cepacia complex (Bcc) isolates amongst non-CF patients has been documented, where inadequate laboratory identification and limited treatment options are considered the main obstacles hindering accurate diagnosis and thus proper therapeutic outcome.The present study aimed to detect the isolation percentage of Bcc from patients in Alexandria Medical University Hospital (AMUH) according to site of infection (specimen), throughout a 6 month period. Out of 2079 specimens submitted to the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…But when compare to Omar et al, the isolation rate was 1.7%, this study shows high prevalence rate. 16 The rate of isolation (7.9%) of this study nearly correlates with the study done by Hadir El Kady et al, found that B. cepacia rate of isolation was 5.3% (8/150). 17 The reasons for varying in results may be attributed to the fact that variation in geographical distribution, sample size, duration of study period, socioeconomic factors, infection control practices in various hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…But when compare to Omar et al, the isolation rate was 1.7%, this study shows high prevalence rate. 16 The rate of isolation (7.9%) of this study nearly correlates with the study done by Hadir El Kady et al, found that B. cepacia rate of isolation was 5.3% (8/150). 17 The reasons for varying in results may be attributed to the fact that variation in geographical distribution, sample size, duration of study period, socioeconomic factors, infection control practices in various hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…[21] [22] [25]but the striking point, in our results, is the high level of ceftazidime resistance (100%) which was not recorded previously, as far as we know. This could be attributed to the excess use of 3 rd generation cephalosporins in our hospital.…”
supporting
confidence: 52%
“…In a Turkish study, ETA was the main source for Bccisolation(58.9%) [21]. However, 62.7% of Bcc were isolated from blood specimens in another study [19] and in a previous Egyptian study, the highest percent (85.7%) of Bcc isolates were from pus specimens [22]. This difference could be attributed to the difference in the clinical conditions of patients along with different hospital wards selected in each study.…”
Section: Discussionmentioning
confidence: 97%
“…(25) More discrepancies are observed as regards piperacillin-tazobactam, where BCC strains in the study of Gautam et al (25) and Dizbay et al (20) were more sensitive to this antibiotic than those tested in the present study showing (86.7%, 61.6%) respectively, and the sensitivity for ciprofloxacin were (83.3%, 46.2%) while none of the 32 B. cepacia complex strains in the present study were sensitive to piperacillin-tazobactam and ciprofloxacin. Another study in Alexandria University 2011, (19) the antibiotic resistance pattern of the 35 BCCstrains as detected by the modified Bauer Kirby single disc diffusion technique revealed that altogether the 35 strains were distributed among 17 different resistance profiles. The largest cluster of strains of identical resistance profile was from patients in the burn unit where 5 strains shared the resistance pattern (TE, SXT, CIP, TZP) and 4 strains shared the resistance pattern (TE, SXT, CIP, TZP, C) with resistance to chloramphenicol as the only added minor variation so the 9 strains could be safely accepted to have almost identical resistance pattern which may implicate a common source or origin.…”
Section: Discussionmentioning
confidence: 99%